Notes on plant bugs (Hemiptera, Heteroptera, Miridae) from Madagascar with a description of new species of the cylapine tribe Fulviini and checklist of Madagascan mirids - Masłowski, Adrian; Baňař, Petr; Carapezza, Attilio; Chérot, Frédéric; Jindra, Zdeněk; Taszakowski, Artur; Wolski, Andrzej (Zootaxa, 2023)
A new species of Fulvius Stål—F. attenboroughi sp. nov.—is diagnosed and described. Schmitzofulvius bigibber Gorczyca, 1998 is redescribed. Photographic images of habitus and genital structures, as well as scanning electron micrographs of selected structures of both species, are provided. Fulvius kerzhneri Gorczyca, 2000 is diagnosed. New records of a few plant bugs species (Collaria elsae Matocq, 2021, C. cf improvisa Reuter, 1893, F. kerzhneri, Linnavuoricoris madagascariensis Chérot, 2013, Malagasycoelum dracula Kim & Jung, 2020 and S. bigibber) from Madagascar and the checklist of Madagascan Miridae are also presented.